Introduction to the systematics and biodiversity of sharks, rays, and chimaeras (Chondrichthyes) of Taiwan - Ebert, David A.; Ho, Hsuan-Ching; White, William T.; de Carvalho, Marcelo R. (Zootaxa, 2013)
All 13 orders of chondrichthyan fishes occur in Taiwanese waters, representing 52 chondrichthyan families (31 shark, 19 batoid, 2 chimaeroid) and 98 genera (64 shark, 31 batoid, 3 chimaeroid). A total of 119 shark, 58 batoid, and 4 chimaera species may occur in the waters surrounding Taiwan, pending taxonomic resolution of some groups. Of the 34 nominally described species from Taiwan, 17 are currently considered valid. The majority of named species occurred during two peak periods in Taiwanese chondrichthyan research; the first between 1959–63, when 13 nominal species were described, of which 7 remain valid today, and a second peak period between 2003–13 when 9 nominal species were described, of which 6 remain valid. The overall species diversity of Taiwan’s chondrichthyan fauna is comparable to that of other adjacent marine zoogeographic hotspots, e.g. Japan (126 shark, 75 batoid, 11 chimaeroid species) and the Philippines (81 shark, 46 batoid, 2 chimaeroid species). The Carcharhiniformes, Squaliformes, Myliobatiformes, and Rajiformes are the most dominant orders in terms of abundance and species-richness within this region. Each of these groups may increase in relative diversity with improved taxonomic resolution resulting from the incorporation of molecular tools and renewed morphological studies. Improved identification of Taiwan’s chondrichthyan fauna will aid in developing better conservation and management practices.